2022
DOI: 10.3390/ph15080918
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of SIRT-1 Pathway by Nanoceria Sheds Light on Its Ameliorative Effect on Doxorubicin-Induced Cognitive Impairment (Chemobrain): Restraining Its Neuroinflammation, Synaptic Dysplasticity and Apoptosis

Abstract: Chemo fog is one of the most serious health concerns encountered by cancer survivors receiving doxorubicin (DOX)-based chemotherapy. Oxidative stress, neuroinflammation, apoptosis and impairment of synaptic plasticity are regarded as the key factors implicated in DOX-induced cognitive impairment. This research aimed to assess the possible neuroprotective effect of cerium oxide nanoparticles (CeNPs) against DOX-induced neurotoxicity. Forty-eight rats were divided into four groups (12 rats/group): control group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…can impact neurotransmitter systems linked to learning and memory. Its regulatory effects on proteins involved in synaptic plasticity, can potentially modulate cognitive outcomes [15]. Additionally, SIRT1 can influence the epigenetic mechanisms (modulation of histone deacetylation) that hold relevance for cognitive function and neuronal vitality [16].…”
Section: Resultsmentioning
confidence: 99%
“…can impact neurotransmitter systems linked to learning and memory. Its regulatory effects on proteins involved in synaptic plasticity, can potentially modulate cognitive outcomes [15]. Additionally, SIRT1 can influence the epigenetic mechanisms (modulation of histone deacetylation) that hold relevance for cognitive function and neuronal vitality [16].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that Sirt1 plays a key role in cognitive performance and regulation of memory function through modulation of BDNF and inhibition of glutamate and the glutamatergic NMDA receptors, which are important factors in the differentiation of hippocampal neuronal cells and synaptic plasticity 90 . Moreover, Sirt1 stimulates the production of antioxidant enzymes and downregulates the expression of proinflammatory markers and apoptotic caspase 3 gene expression, which has been suggested to play a role in positive cognitive effects 91 .…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy-induced cognitive impairment or 'chemobrain' has been established as a secondary effect of chemotherapy treatment and it may persist for the following years, with a prevalence between 28% (Schagen, Muller et al 2002) and 75% (Wieneke and Dienst 1995). The cognitive domains reported more often to be impaired in those clinical studies were verbal memory, psychomotor function (Ahles, Saykin et al 2002), visual memory, visuospatial and verbal learning (Castellon, Ganz et al 2004), memory function and attention (Wefel, Lenzi et al 2004), suggesting extensive impairment mainly to the prefrontal cortex (PFC) and hippocampal formation (HF) (Taha, Elazab et al 2022). Doxorubicin (DOX) is one of the most frequently used chemotherapeutic agents in cancer therapy.…”
Section: Introductionmentioning
confidence: 98%